Clinical impact of high-sensitivity C-reactive protein during follow-up on long-term adverse clinical outcomes in patients with coronary artery disease treated with percutaneous coronary intervention. Issue 1 (January 2019) - Shitara, Jun; Ogita, Manabu; Wada, Hideki; Tsuboi, Shuta; Endo, Hirohisa; Doi, Shinichiro; Konishi, Hirokazu; Naito, Ryo; Dohi, Tomotaka; Kasai, Takatoshi; Okazaki, Shinya; Isoda, Kikuo; et al.
Highlights: We examined the prognostic value of high-sensitivity C-reactive protein (hs-CRP) at follow-up angiography after percutaneous coronary intervention (PCI). Elevated levels of hs-CRP during follow-up are associated with risk of adverse cardiac events and mortality after PCI. Hs-CRP may be a secondary prevention biomarker in coronary artery disease patients after PCI. Abstract: Introduction: C-reactive protein (CRP) is an established marker for vascular inflammation and predictor of adverse cardiovascular events, but the prognostic value of preprocedural CRP in coronary artery disease (CAD) patients who have undergone percutaneous coronary intervention (PCI) remains controversial. Furthermore, the impact of CRP levels during follow-up in CAD patients after PCI on long-term adverse clinical outcomes is uncertain. We evaluated the association between high-sensitivity (hs)-CRP values at follow-up angiography and long-term clinical outcomes in CAD patients after coronary intervention. Methods: We prospectively enrolled 3507 consecutive CAD patients who underwent first PCI between 1997 and 2011 at our institution. We identified 2509 patients (71.5%) who underwent follow-up angiography (6–8 months after PCI). Of those, 1605 patients (45.8%) who had data available for hs-CRP at follow-up angiography were stratified into three groups according to tertiles of hs-CRP level at the time of follow-up angiography. The primary endpoint was composite of all-cause death and non-fatal acute coronary syndrome (ACS). Results: Median follow-up was 1716 days. The cumulative incidence of all-cause death and ACS differed significantly among groups (log-rank, p = 0.0002). Multivariate Cox regression analysis showed that a higher hs-CRP level at follow-up angiography was associated with a greater risk of all-cause death and ACS [adjusted hazard ratio (HR) for all-cause death and ACS 2.14, 95% confidence interval (CI) 1.43–3.27, p = 0.0002. Conclusion: Elevated hs-CRP levels during follow-up were significantly associated with higher frequencies of adverse long-term clinical outcomes in patients with CAD after PCI.